Left. No. 76, What they say about the Beveridge Report ([London : Controversy Pub. Co.])
1943-01 1943 1940s 8 pages DOCUMENTARY What They Say About the Beveridge Report Full support for the Beveridge Report came from The Times, Manchester Guardian, News Chronicle, Daily Mirror and Daily Herald. The Guardian (2.12.42): "It is a big and fine thing, the charting of a great piece of national reconstruction ... If we do not get something like it into being before the war is over, the political consequences will be serious. Instead of victory we shall have suffered defeat." The News Chronicle (2.12.42): "If victory is to be given meaning, the principles underlying this primary act of justice must be achieved, and the plans for putting it into legislative operation must be made now, while the war is on." The Times: Leader (2.12.42). — Sir William Beveridge and his colleagues have put the nation deeply in their debt, not merely for a confident assurance that the poor need not always be with us, but for a masterly exposition of the ways and means whereby the fact and the fear of involuntary poverty can be speedily abolished altogether. The implications of its proposals, viewed as a whole, reach far. Yet they involve no new departure in principle from the policies and methods which have characterised the development of the British social services during the last half-century. The prescription is for "a British revolution," in which the experience of the past and its tested institutions as well as the creative insight of adventurous minds both have their full shares. The Report is a momentous document which should and must exercise a profound and immediate influence on the direction of social change in Britain. Some modifications in detail may prove necessary or unavoidable, but the central proposals of the report must surely be accepted as the basis of Government action. The minimum social standards on which the report insists are moderate enough to disarm any charge of indulgence. They are designed, not to undermine those incentives to effort which are the vital springs of our social system, but to provide, in place of a quagmire of poverty and insecurity, the firm foundation which will give to men and women the freedom to rise by their own exertions. Full support also came from the Economist, the Financial News ("The proposed benefits are adequate, but they are certainly not lavish. Nor is the estimated cost at all prohibitive"), the Observer and the Spectator. The Lancet declared itself not afraid of a State medical service. The Catholic Herald found its own reasons for giving support, and Major T. L. Dugdale, chairman of the Conservative Party, tried to annexe the Report for his own Party. 6 172/BE/7